2003
DOI: 10.1074/jbc.m211821200
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonian Mimetics Induce Aspects of Unfolded Protein Response in Death of Dopaminergic Neurons

Abstract: Genes associated with Parkinson's disease (PD) have suggested a role for ubiquitin-proteasome dysfunction and aberrant protein degradation in this disorder. Inasmuch as oxidative stress has also been implicated in PD, the present study examined transcriptional changes mediated by the Parkinsonism-inducing neurotoxins 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenylpyridinium (MPP ؉ ) in a dopaminergic cell line. Microarray analysis of RNA isolated from toxin treated samples revealed that the stress-induced tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
262
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(286 citation statements)
references
References 58 publications
23
262
0
1
Order By: Relevance
“…Mutation of parkin, that is an E3 ubiquitin ligase, is one of the major causes of familial Parkinson's disease. 103 Parkin is induced by ER stress, and overexpression of parkin confers resistance to both ER stress and mutant a-synuclein-induced toxicity. 104,105 Furthermore, accumulation of polyglutamine-containing proteins was found to cause ER stress, presumably due to saturation of the cytosolic protein degradation system.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…Mutation of parkin, that is an E3 ubiquitin ligase, is one of the major causes of familial Parkinson's disease. 103 Parkin is induced by ER stress, and overexpression of parkin confers resistance to both ER stress and mutant a-synuclein-induced toxicity. 104,105 Furthermore, accumulation of polyglutamine-containing proteins was found to cause ER stress, presumably due to saturation of the cytosolic protein degradation system.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…36,37 Compounds, such as 6-hydroxydopamine (6-OHDA) and N-methyl-4-phenyl-1, 2,3,6-tetrahydroyridine or its active derivative, MPP þ , induce oxidative stress and impair mitochondrial respiration and energy metabolism. Recent studies with cultured neuronal cells, including dopaminergic neurons, showed that these compounds trigger ER stress and induce a number of genes.…”
Section: Er Stress and Parkinson's Diseasementioning
confidence: 99%
“…Recent studies with cultured neuronal cells, including dopaminergic neurons, showed that these compounds trigger ER stress and induce a number of genes. 36,37 Gene profiling revealed that both ER chaperones and other components of the UPR such as the transcription factor, CHOP/Gadd153 were upregulated in exposed cells, in addition to the phosphorylation of the ER stress kinases, IRE and PERK. 36,37 These changes were specific for the two PD mimetic and rotenone, a mitochondrial inhibitor that causes degeneration of dopaminergic neurons but not with other agents.…”
Section: Er Stress and Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations